Hubungan Perilaku Overprotective Orang Tua Terhadap Penyesuaian Diri Remaja - Ansaris, Faizal (Fakultas Psikologi Universitas Teknologi Sumbawa, 2024)
Overprotective behavior of parents towards adolescents determines how adolescents develop in adjusting to their environment and others. In this overprotective behavior, parents give excessive control to adolescents in adjusting themselves. The aim of this study was to investigate the relationship between overprotective parental behavior and adolescents' ability to adapt. To fulfill this goal, data was collected using questionnaires distributed to 65 participants, consisting of second-semester students from the psychology department at the University of Muhammadiyah Gresik. This research employed a quantitative approach. Data collection involved questionnaires on parental overprotectiveness and adolescent self-adjustment. The data analysis process included validity and reliability testing. The results indicated a significant connection between parental overprotective behavior and adolescent self-adjustment.